A gestão das políticas ambientais em São Luís (MA): os conflitos socioambientais e territoriais na APA Maracanã - Barbosa Filho, William (2019)
This dissertation analyzes the management of environmental policies in the state of Maranhão, identifying the factors responsible for the suppression and spatial (re) configuration in the Conservation Units, the institutional instruments of control and participative management in the implementation of these policies. From these factors we proceeded to examine the social economic implications, from the occupation of the area to the creation of the Conservation Unit, the context and effectiveness of environmental legislation and the advance of private capital over protected areas. The study clipping is the Maracanã Environmental Protection Area in the industrial district of São Luís was the subject of a literature review and field research. From the methodological point of view, we used a semi-structured interview with 02 managers and 05 counselors of the Maracanã APA in order to know the reality beyond the mere appearance. In the field research, interviews with participants from the APA advisory council and the State Municipal Environmental Secretariat, put us in front of the concrete reality of APA Maracanã and allowed the presentation of the results extracted from the interviewees' reports in which it was found that The main determinants of the suppression dynamics of Conservation Units in Maranhão are the urban expansion movements in conjunction with real estate speculation, agribusiness and industrial activities driven by developmental policies